EKSISTENSI KOMUNITAS HANDLETTERING SURAKARYA DI SURAKARTA - Priya Aji, Rizky; Murtono, Taufik (CITRAWIRA : Journal of Advertising and Visual Communication, 2020)
The existence of the Surakarya Handlettering Community in Surakarta. This community is a learning group to write handlettering art in Surakarta, which was formed in 2014, where currently dozens of members have joined who have creativity and expertise in the art of handlettering. This research uses descriptive qualitative method which aims to examine how the role of the Surakarya Community in the development of handlettering in Surakarta and how to develop the style and work of handlettering in Surakarta. Data analysis was carried out by interviewing several community members, direct observation by means of observation and making a questionnaire, and documenting community activities in the form of pen meet-ups. This research found that the existence of communities in popularizing the arts of handlettering and calligraphy was formed through two aspects, namely the role through several internal and external activities such as exhibitions, belcor (belmen corner), pen meet up, ngangsu kaweruh and lettering camp. The second aspect is in the form of alternative styles and handlettering works that have been developed covering 7 (seven), namely: decorative lettering, script lettering, chalk lettering, watercolor lettering, calligraphy brushes, modern calligraphy and calligraphy blackletter. The art of handlettering is in the form of murals that decorate several cafes and corners of the city of Surakarta, besides the work of the Surakarya community which is applied in the form of media such as helmets, tote bags, packaging, pillow covers and t-shirts. For the Surakarya community in the future it will be more developed and promote the community in cultivating the arts of handlettering and calligraphy both at the local and national levels.